2019
DOI: 10.1155/2019/9751923
|View full text |Cite
|
Sign up to set email alerts
|

KIF23 Promotes Gastric Cancer by Stimulating Cell Proliferation

Abstract: Gastric cancer (GC) is one of the most aggressive malignant tumors with low early diagnosis and high metastasis. Despite progress in treatment, to combat this disease, a better understanding of the underlying mechanisms and novel therapeutic targets is needed. KIF23, which belongs to the KIF family, plays a vital role in various cell processes, such as cytoplasm separation and axon elongation. Nowadays, KIF23 has been found to be highly expressed in multiple tumor tissues and cells, suggesting a potential link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
4
40
0
1
Order By: Relevance
“…Overexpression of KIF23 in non-small cell lung cancer (NSCLC) governs the crucial functions of KIF23 in regulating the cancerous properties of the cells [16]. KIF23 has been found to increase in GC and silencing KIF23 suppressed cell proliferation recently [5]. Consistently, the public datasets and our experimental results confirmed that KIF23 was upregulated in GC tissues and that expression of KIF23 was relatively high in advanced tumor tissues.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overexpression of KIF23 in non-small cell lung cancer (NSCLC) governs the crucial functions of KIF23 in regulating the cancerous properties of the cells [16]. KIF23 has been found to increase in GC and silencing KIF23 suppressed cell proliferation recently [5]. Consistently, the public datasets and our experimental results confirmed that KIF23 was upregulated in GC tissues and that expression of KIF23 was relatively high in advanced tumor tissues.…”
Section: Discussionsupporting
confidence: 84%
“…Kato T et al verified that KIF23 was upregulated in lung cancer and predicted a poor clinical outcome [4]. Recently, Xiaolong Li found that KIF23 upregulated in GC and silencing KIF23 suppressed cell proliferation [5]. However, to date, the mechanisms of KIF23 in cancer remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, KIF11 was supposed to be the novel therapeutic target of meningioma. Moreover, KIF23 was highly expressed in gastric cancer cells and it accelerated the progression of gastric cancer [17]. In our research, we investigated the function of KIF15 in breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that KIF23, as a member of the kinesin superfamily 6, is highly expressed in gastric cancer and is positively correlated with pTNM stage and poor prognosis. Knocking down KIF23 can inhibit the proliferation of gastric cancer cells [28]. Sun [29] [30].…”
Section: Discussionmentioning
confidence: 99%